Discovery of GW870086: a potent anti‐inflammatory steroid with a unique pharmacological profile. (21st June 2013) - Uings, I J; Needham, D; Matthews, J; Haase, M; Austin, R; Angell, D; Leavens, K; Holt, J; Biggadike, K; Farrow, S N
<x xml:space="preserve">Abstract</x> Background and Purpose Glucocorticoids are highly effective therapies for a range of inflammatory diseases. Advances in the understanding of the diverse molecular mechanisms underpinning glucocorticoid action suggest that anti‐inflammatory molecules with reduced side effect liabilities can be discovered. Here we set out to explore whether modification of the 17α position of the steroid nucleus could generate molecules with a unique pharmacological profile and to determine whether such molecules would retain anti‐inflammatory activity. Experimental Approach The pharmacological properties of GW870086 were compared with fluticasone propionate (FP) using a range of cellular and in vivo model systems, including extensive gene expression profiling. Key Results GW870086 repressed inflammatory cytokine release from lung epithelial cells in a similar manner to FP but antagonized the effect of dexamethasone on MMTV‐driven reporter gene transactivation. GW870086 had a strong effect on the expression of some glucocorticoid‐regulated genes (such as PTGS2), while having minimal impact on the expression of other known target genes (such as SGK). GW870086 retained the ability to strengthen tight junctions in epithelial cell culture but, unlike FP, was unable to protect the culture from elastase‐mediated damage. In murine models of irritant‐induced contact dermatitis and ovalbumin‐induced allergic inflammation, GW870086 showed comparable anti‐inflammatory efficacy to FP. Conclusion and Implications GW870086 is a potent anti‐inflammatory compound with a unique ability to regulate only a subset of those genes that are normally affected by classical glucocorticoids. It has the potential to become a new topical steroid with a different safety profile to existing therapies.